Mono-BHT heteroleptic magnesium complexes: synthesis, molecular structure and catalytic behavior in the ring-opening polymerization of cyclic esters. Issue 36 (4th September 2017) - Nifant'ev, I. E.; Shlyakhtin, A. V.; Bagrov, V. V.; Minyaev, M. E.; Churakov, A. V.; Karchevsky, S. G.; Birin, K. P.; Ivchenko, P. V.
Abstract : Dimeric BHT-alkoxy magnesium complexes are able to catalyze ROP of lactones and lactides by the binuclear mechanism. Abstract : Numerous heteroleptic 2, 6-di- tert -butyl-4-methylphenolate (BHT) magnesium complexes have been synthesized by treatment of (BHT)MgBu(THF)2 with various alcohols. Molecular structures of the complexes have been determined by X-ray diffraction. The magnesium coordination number in [(BHT)Mg(μ-OBn)(THF)]2 (3 ) and [(BHT)Mg(μ-O- tert -BuC6 H4 )(THF)]2 (4 ) is equal to 4. Complexes formed from esters of glycolic and lactic acids, [(BHT)Mg(μ-OCH2 COOEt)(THF)]2 (5 ) and [(BHT)Mg(μ-OCH(CH3 )COOCH2 COO t Bu)(THF)]2 (6 ) contain chelate fragments with pentacoordinated magnesium. Compounds3–6 contain THF molecules coordinated to magnesium atoms. Complex {(BHT)Mg[μ-O(CH2 )3 CON(CH3 )2 ]}2 (7 ) does not demonstrate any tendency to form an adduct with THF. It has been experimentally determined that complexes3 and5 are highly active catalysts of lactide polymerization. The activity of4 is rather low, and complex7 demonstrates moderate productivity. According to DOSY NMR experiments, compounds3 and5 retain their dimeric structures even in THF. The free energies of model dimeric [(DBP)Mg(μ-OMe)(Sub)]2 and monomeric (DBP)Mg(OMe)(Sub)2 products on treatment of [(DBP)Mg(μ-OMe)(THF)]2 with a series of σ-electron donors (Sub) have been estimated by DFT calculations. These results demonstrate that the substitution of THF by Sub in a dimeric molecule is an energetically allowed process, whereas the dissociation of dimers is energetically unfavorable. DFT modeling of ε-CL and (dl )-lactide ROP catalyzed by dimeric and monomeric complexes showed that a cooperative effect of two magnesium atoms occurs within the ROP for binuclear catalytic species. A comparison of the reaction profiles for ROP catalyzed by binuclear and mononuclear species allowed us to conclude that the binuclear mechanism is favorable in early stages of ROP initiated by dimers3 and5 .